Proposal for a model of tourist valuation of gusle and singing to the accompaniment of the gusle in the rural area of the Zadar County - Vištica, Dario (Oeconomica Jadertina, 2020)
In Zadar County, there is a large difference in development between coastal and rural areas. Those areas located on the Adriatic coast are much more developed than the rural ones. The development of various forms of tourism has a significant impact on the above, given that the scientific and professional literature states that tourism development affects significantly the development of the area itself. The paper deals with the tourist valuation of gusle and guslar performance, traditional musical instruments and the ways of singing a rich cultural heritage. Through the tourist valuation of gusle and guslar performance, different types of tourist products can be created, while also contributing to the preservation of the intangible cultural heritage of Zadar County. Gusle and guslar performance are important, and at the same time they represent an unexploited form of the tourist offer of Zadar County, therefore an initiative is required by key stakeholders in tourism for better and more efficient tourist valuation of gusle and guslar performance. The paper presents a model of tourist valuation of gusle and guslar performance at the level of the rural area of Zadar County.